Once Upon a Time There Was an Indian - Arij, Ouweneel (CEDLA, 2018)
Alas de maguey. La lucha de Eufrosina Cruz Mendoza, by Marta Gómez-Rodulfo, with a preface by Elena Poniatowska, 2012.Embers of the Past. Essays in Times of Decolonization, by Javier Sanjinés C., with a foreword by Walter D. Mignolo; translated by David Frye, 2013.The Village Is Like a Wheel: Rethinking Cargos, Family and Ethnicity in Highland Mexico, by Roger Magazine, 2012.